2020
DOI: 10.3389/fpls.2020.576581
|View full text |Cite
|
Sign up to set email alerts
|

Expression Landscape of circRNAs in Arabidopsis thaliana Seedlings and Adult Tissues

Abstract: RNA-seq is currently the only method that can provide a comprehensive landscape of circular RNA (circRNAs) in the whole organism and its particular organs. Recent years have brought an increasing number of RNA-seq-based reports on plant circRNAs. Notably, the picture they revealed is questionable and depends on the applied circRNA identification and quantification techniques. In consequence, little is known about the biogenesis and functions of circRNAs in plants. In this work, we tested two experimental and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…This might be explained by the fact that polyA+RNase R+ rRNA – treatment method can more efficient at removing linear RNAs, thus leading to an increased the resolution of the analysis. This result has also been confirmed in Philips A, et al [ 36 ] study. Nevertheless, the number of identified circRNA candidates by using polyA+RNase R and rRNA – +polyA+RNase R enrichment methods were not difference with compared to rRNA depletion group.…”
Section: Discussionsupporting
confidence: 81%
“…This might be explained by the fact that polyA+RNase R+ rRNA – treatment method can more efficient at removing linear RNAs, thus leading to an increased the resolution of the analysis. This result has also been confirmed in Philips A, et al [ 36 ] study. Nevertheless, the number of identified circRNA candidates by using polyA+RNase R and rRNA – +polyA+RNase R enrichment methods were not difference with compared to rRNA depletion group.…”
Section: Discussionsupporting
confidence: 81%
“…RNA sequencing technology is currently the only method capable of providing a complete landscape of circRNAs throughout the body and in specific tissue areas ( Philips et al, 2020 ). In particular, ribo-minus RNA-seq, has allowed identifying new change in circRNAs expression and also investigate the roles of these circRNAs in the condition of interest ( Cooper et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The following information is available for each circRNA: (i) the study in which the datasets were generated, (ii) plant line and organ in which circRNAs were identified, (iii) the average score, computed for all circRNAs according to the same procedure, (iv) the individual component scores and (v) information regarding whether a circRNA was confirmed with RNase R experiments. It is worth mentioning that we introduced a novel ‘reproducibility’ criterion in At-C-RNA, as in our previous studies, and we showed that most circRNAs in A. thaliana are produced spontaneously and thus possibly carry no biological function ( 11 ). It is important to highlight the reproducible circRNAs, which may have functional potential and thus are especially important to the wide range of studies.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, we compared the sources used by other plant circRNA databases and we chose those that met our criteria. In total, we utilized third-party data from eight studies (100 SRA files) and two datasets (110 SRA files) from our previous studies ( 11 , 12 ). All analyzed datasets are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation